Pengembangan Bahan Ajar Mata Pelajaran Fiqih Dalam Memotivasi Belajar Siswa di Madrasah Tsanawiyah Negeri 2 Kota Jambi - Muhammad Zaki Rahman; Minnah El Widdah; Najmul Hayat (Syntax Idea)
Teaching materials are closely related to learning in the classroom, which in teaching materials requires innovation according to needs. This also happened to Madrasah Tsanawiyah Negeri 2 Jambi City, one of which is the development of fiqh teaching materials in motivating student learning. The formulation of the problem in this study is: 1) How is the motivation of student learning in Madrasah Tsanawiyah Negeri 2 Jambi City?, 2) How are the obstacles and solutions of fiqh teachers in developing teaching materials for fiqh subjects in motivating student learning in Madrasah Tsanawiyah Negeri 2 Jambi City?, 3) How is the development of teaching materials for fiqh subjects in motivating student learning in Madrasah Tsanawiyah Negeri 2 Jambi City?. The objectives of the development of this teaching material are 1) Producing fiqh teaching materials in class XI Madrasah Tsanawiyah Negeri 2 Jambi City. 2) Describe and test the feasibility of jurisprudence teaching materials in class XI Madrasah Tsanawiyah Negeri 2 Jambi City. 3) Testing the effectiveness of fiqh teaching materials in class XI Madrasah Tsanawiyah Negeri 2 Jambi City. The type of research used is Research and Devolopment, which refers to the Borg and Gall model which is divided into 10 steps, namely: (1) research and data collection, (2) planning, (3) product draft development, (4) initial field trials, (5) revising trial results, (6) field trials, (7) improving field test products, (8) field implementation tests, (9) improvement of product results, and (10) dissemination and implementation, but at this stage researchers only use methods 1-7 due to the limited time that researchers have. The results of the development assessment can be concluded that the teaching materials developed by researchers in the form of jurisprudence teaching materials use the research and development (R&D) model of Borg and Gall. The size of the teaching material product developed is a paper size of 23 cm long and 17 cm wide, more variations are added on the cover, as well as a balance sheet image on the back. And don't forget to include interesting colors. Then after the last revision stage, the color was changed to green to make it more attractive for the target product, namely grade IX students of Madrasah Tsanawiyah, so that it looks more simple and elegant, the postulates of the Qur'an and hadith were added, then writing Arabic using Traditional Arabic size 14 pt. This teaching material is validated by one expert, namely a content / material expert, a linguist, and two design experts. From the feasibility validation test, an average of 85.32% was produced with the criteria that the teaching materials were worthy of being continued in this research and development because they met the minimum standards.